2017
DOI: 10.2147/nss.s136467
|View full text |Cite
|
Sign up to set email alerts
|

Total sleep time, alcohol consumption, and the duration and severity of alcohol hangover

Abstract: IntroductionAn evening of alcohol consumption often occurs at the expense of sleep time. The aim of this study was to determine the relationship between total sleep time and the duration and severity of the alcohol hangover.MethodsA survey was conducted among Dutch University students to collect data on their latest alcohol hangover. Data on alcohol consumption, total sleep time, hangover severity, and duration were collected. Alcohol consumption and hangover severity and duration were compared for participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
7
22
1
Order By: Relevance
“…For this, we asked groups of 4 to 8 participants to join a drinking session on a Friday or Saturday evening (starting at 20:00 and ending at approximately 01:30/02:00). The subsequent hangover session was planned for the following morning (that is either on Saturday or on Sunday, starting between 09:00 and 11:00) to slightly reduce sleep duration, as the amount of sleep time is negatively related to hangover severity [35].…”
Section: Experimental Designmentioning
confidence: 99%
“…For this, we asked groups of 4 to 8 participants to join a drinking session on a Friday or Saturday evening (starting at 20:00 and ending at approximately 01:30/02:00). The subsequent hangover session was planned for the following morning (that is either on Saturday or on Sunday, starting between 09:00 and 11:00) to slightly reduce sleep duration, as the amount of sleep time is negatively related to hangover severity [35].…”
Section: Experimental Designmentioning
confidence: 99%
“…The number of smoked cigarettes was recorded as well, as previous research has shown an interaction between smoking and hangover [18]. To capture possible effects of sleep [14,19,20], total sleep time was recorded as well as the (consciously perceived) number of nightly awakenings. Sleep quality was rated on an 11-point scale ranging from 0 (very poor) to 10 (excellent) [21,22].…”
Section: Data Collectionmentioning
confidence: 99%
“…Links between heavy drinking and poor sleep have also been reported in college students (Miller et al, 2017) and adults (van Schrojenstein Lantman, Mackus, Roth, & Verster, 2017), with poorer sleep associated with extended and more severe hangover symptoms (van Schrojenstein Lantman, Mackus, et al, 2017) and increased next day sleepiness (van Schrojenstein Lantman, Roth, Roehrs, & Verster, 2017). Sleep has also been examined in outpatients following treatment for alcohol dependence (Currie, Clark, Rimac, & Malhotra, 2003;Foster & Peters, 1999) and may play a role in the development of a subsequent mood or psychiatric disorder (Roberts, Roberts, & Duong, 2008).…”
Section: Introductionmentioning
confidence: 99%